STUDI EKSPERIMENTAL PENGARUH PENCITRAAN VISUAL IKLAN LABEL DESAINER TERHADAP SIKAP MENYUKAI IKLAN DAN NIAT BELI - Inda Premordia; Agus Maulana; Febriantina Dewi (School of Business, Bogor Agricultural University (SB-IPB), 2008)
The current focus of this thesis is to determine, using the Stimulus-Organism-Response theory, (1) which type of user imagery (embodied imagery or static imagery) leads the consumer to greater hedonic and behavioral responses; (2) whether usage imagery intensifies this relationship; and (3) what strategies are best to designer label ads communication effectiveness on fashion magazine. 40 female consumers of fashion magazine and designer label were recruited to participate voluntarily in the study. Methodologically, participants were required to answers a series of questions after being exposed a stimuli of pictures. Influence variables evaluated in the model included: Imagery responses (Quantity, Vividness, Ease); Emotion as mediator; Advertising liking; Purchase intention; and Individual Characteristics. Consist of two study, study 1 of this thesis served as a pre-test to build the experimental material. Whereas, study 2 served as an experimental study that addresses the current focus of this thesis. Analyzed with series of Manova, results indicated that when presented independently of usage imagery, embodied user imagery can enhance consumer’s hedonic impressions and affect purchase intention. Usage imagery however failed to prove any influences. When presented together, such combinations of brand imagery as embodied user imagery and usage imagery as well as static user imagery and usage imagery didn’t bring the consumer to greater hedonic impressions and purchase intention. The findings could be used to predict purchase intention of designer label’s product. Retailers and marketers of designer labels or interested researchers could use the model based on consumer attitude and behavioral intentions.